Sport Management Competency: A Literature Review : 運動管理技能之文獻探討 - TOH, Kian Lam (Asian Journal of Physical Education & Recreation, 1998)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Every year, millions of dollars have been spent on a booming industry called sport. An increase in the demand for management personnel in the sport related settings is therefore foreseeable. However, research in sport management competency is still very scarce locally. This review not only aims at presenting some of the related findings but more importantly, tries to foment some interests in conducting this area of study locally. 隨著運動事業的蓬勃發展，運動管理人員需求的增加也是必然的。然而在本地，有關運動管理技能的研究幾乎是少之又少；本文獻探討的目的不僅爲提供一些相關的研究結果而已，最重要的還是希望能夠喚起大家以本地爲對象，多多進行這方面的研究。